Qualitative Performance Indicators of a Ripping-and-Separating Machine for Soil Cultivation - Yu. N. Syromyatnikov (Сельскохозяйственные машины и технологии)
Pre-sowing soil cultivation aims at forming such a soil structure, which will allow increasing the yield. (Research purpose) To determine the qualitative indicators of an experimental soilcultivating ripping-and-separating rotary machine for optimizing the ploughed soil layer, modifying the structure and density of the cultivated soil layer in accordance with the agronomic requirements. (Materials and methods) The author has studied physical and mechanical properties of the soil after its spring cultivation in the conditions of bare (black) fallow. Soil structure and aggregate composition depending on the type of cultivation, the density of soil layers at different times, the dynamics of soil moisture changes in the layers for two months after its spring cultivation have been analyzed as well. (Results and discussion) The author has studied the operation of a soil tillage ripping-and-separating machine on the soil layer, which is separated after processing into four sublayers: over-seed, seed, under-seed and subsurface ones. Soil fragments (lumps) of a size larger than 20 mm have been completely removed from the over-seed sublayer. The most valuable soil structure in agronomic terms is formed in the seed sublayer, where the size of individual components does not exceed three times the size of seeds, the density of the under-seed sublayer is up to 1.25 grams per cubic centimeter. The subsurface sublayer has a density of not more than 1.3 grams per cubic centimeter and a hardness of more than 3 MPa in the plow sole, which is provided by the main tillage operations. The information for the study has been obtained as a result of the analysis of literary sources. (Conclusion) The experimental machine for optimizing the agrophysical properties of the ploughed soil layer allows increasing the structural coefficient by about 2.5 times as compared with traditional cultivators. It has been found that soil cultivation with a ripping-and-separating tillage machine allows to improve the methods of pre-sowing cultivation to improve its agrotechnical characteristics, skip pre-sowing harrowing and cultivation and prepare the soil for sowing in one run.